Gilpinia hakonensis and similar species in Japan and ovipositors of five European Gilpinia species (Hymenoptera, Diprionidae) - Hara, Hideho; Smith, David R.; Shinohara, Akihiko (Zootaxa, 2021)
The following three Japanese conifer sawflies are described or redescribed with figures of the ovipositors and male genitalia: Gilpinia hakonensis (Matsumura, 1912) from Honshu and Kyushu, Japan and Korea, G. amamiana Okutani, 1965, from Amami Oshima Island and Tokunoshima Island, Japan and G. okinawa sp. nov. from Okinawa Island, Japan. These three species are very similar and belong to the G. socia group. The lectotype for Lophyrus hakonensis Matsumura, 1912 is designated. The males of G. hakonensis and G. amamiana are described for the first time. Gilpinia fukudai (Togashi, 1964) from Honshu, Japan, is a new synonym of G. hakonensis. The host plant of G. hakonensis is Pinus densiflora Siebold et Zucc. Gilpinia amamiana is newly recorded from Tokunoshima Island. For comparison, ovipositors of five European species of the G. socia group, G. abieticola (Dalla Torre, 1894), G. frutetorum (Fabricius, 1793), G. laricis (Jurine, 1807), G. socia (Klug, 1812) and G. variegata (Hartig, 1834), are described and figured. The ovipositors of G. frutetorum, G. laricis and G. variegata are figured for the first time. Gilpinia laricis is newly recorded from Bulgaria.